Progressive study of the effect of superfine green tea, soluble tea, and tea polyphenols on the physico-chemical and structural properties of wheat gluten in noodle system. (5th March 2020) - Han, Chuan-Wu; Ma, Meng; Zhang, Hai-Hua; Li, Man; Sun, Qing-Jie
Highlights: Polyphenol is a key component in tea to improve gluten strength and noodle texture. Tea polyphenols enhanced hydrogen bonds and hydrophobic interactions in gluten. Dynamic MWD of gluten proteins in tea noodles during cooking were detected. Tea polyphenols caused the aggregation of protein molecular chains. Abstract: In this study, the improving effects of green tea powder, soluble tea, and tea polyphenols on the mixing and tensile qualities of dough and texture of tea-enriched noodles, as well as the physico-chemical and structural properties of gluten proteins were progressively investigated. Dough strength and noodle texture were significantly increased by all the three tea products. Tea polyphenols in particular presented the most effective improvement with highest dough stability, resistance, and noodle chewiness. SEM indicated that tea products all induced a more developed gluten network, and polyphenol noodle showed the most continuous and ordered structure. FT-IR and fluorescence spectrum indicated that tea polyphenols promoted an enhancement in α -helix structure and the hydrophobic interactions. Tea polyphenols induced the SH/SS interchange during processing and cooking, and enhanced the water-solids interaction in noodles. AFM results showed that polyphenols induced the polymerization of gluten protein molecular chains, with increased chain height and width.